1947
DOI: 10.1103/physrev.72.967
|View full text |Cite
|
Sign up to set email alerts
|

The Isotopic Constitution of Lanthanum and Cerium

Abstract: The isotopic abundances of lanthanum and cerium have been determined by means of a mass spectrometer. In addition to the known lanthanum isotope of mass 139, a new isotope of mass 138 and abundance 0.089 percent has been discovered. Since this isotope is isobaric with two neighboring stable isotopes it should be radioactive. No activity was observed. Upper limits for the non-existence of other lanthanum isotopes were determined. The abundances of cerium isotopes of masses 136, 138, 140, and 142 were shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…The "g" annotation arises from the presence of naturally occurring fission products found in fossil reactors at Gabon, southwest Africa. In its 1961 report [22], CAWIA recommended A r (Ce) = 140.12 based on the average value of the mass-spectrometric measurements by Inghram et al [424] and Hibbs [354], which were in good agreement with earlier chemical determinations. As a result, CAWIA in 1969 [4] assessed the uncertainty U[A r (Ce)] to be 0.01.…”
Section: Cs Caesium (Cesium)supporting
confidence: 66%
See 2 more Smart Citations
“…The "g" annotation arises from the presence of naturally occurring fission products found in fossil reactors at Gabon, southwest Africa. In its 1961 report [22], CAWIA recommended A r (Ce) = 140.12 based on the average value of the mass-spectrometric measurements by Inghram et al [424] and Hibbs [354], which were in good agreement with earlier chemical determinations. As a result, CAWIA in 1969 [4] assessed the uncertainty U[A r (Ce)] to be 0.01.…”
Section: Cs Caesium (Cesium)supporting
confidence: 66%
“…As a result, CAWIA in 1969 [4] assessed the uncertainty U[A r (Ce)] to be 0.01. Consideration was also given to a determination by Umemoto [421], which, with atomic masses [49], calculates to A r (Ce) = 140.1148, compared with 140.1048 for Inghram et al [424] and 140.124 5 for Hibbs [354]. Though the atomic weight of Ce of 140.11(2) might be a slightly better value, CAWIA has not seen sufficiently compelling reasons to make a change until new results became available.…”
Section: Cs Caesium (Cesium)mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al [14] included measurements of seven different samples from China, the United States, and Japan in their study and found no evidence for measurable variations. The previous value, A r (Nd) = 144.24(3), was based on the average of isotope amount measurements of Inghram et al [15] and Walker and Thode [16] arriving at a value of 144.24 that was adopted in 1961 [17] and an evaluated uncertainty was included in 1969 [18]. Historical values of A r (Nd) include [6]: 1894, 140.…”
Section: Neodymiummentioning
confidence: 99%
“…The previous atomic weight value was A r (La) = 138.9055(2), which was based on the average of the isotope amount data of Inghram et al [15] and White [20]. Historical values of A r (La) include [6] …”
Section: Lanthanummentioning
confidence: 99%